Website Based Baralau Village Information System Design - Nursiwa, Miftahul Jannah; Ardi Ramadhan; Ita Fitriati; Amelia Putri (Yayasan Insan Mulia Bima, 2024)
Current village development cannot be separated from the increase in information technology, starting from the use of mobile phones to smart phones (smart phones) to the use of the internet with various technological features intended to support people in their daily activities. Information and communication technology provides various benefits for public activities, one of which is to facilitate administrative matters in data management. With the support of information technology, data is easily conveyed to both rural and urban residents. This research was carried out in several stages, namely the first stage was conducting interviews with the Baralau village government, then the second stage was collecting data which would become a reference in developing the Baralau village information system website and the final stage was designing and developing the website. In the website design and development stages, researchers used the waterfall method. The results of this research are that the village can monitor the status of letter submissions in real-time, provide notification to the community about the status of the application, and increase the transparency of the administrative process. ABSTRAK Perkembangan desa dikala ini tidak lepas dari meningkatnya teknologi informasi, mulai dari pemanfaatan telepon genggam hingga telepon cerdas (telepon pintar) hingga pemanfaatan internet dengan beragam fitur teknologi yang dimaksud bakal mendukung khalayak dalam berkegiatan setiap hari. Teknologi informasi dan juga komunikasi memberikan beragam manfaat buat aktivitas khalayak salah satunya untuk memudahkan soal administrasi dalam manajemen data dengan dukungan teknologi informasi maka data mudah tersampaikan dengan baik pada penduduk pedesaan maupun perkotaan. Penelitian ini dilakukan dalam beberapa tahapan yaitu tahap pertama adalah melakukan wawancara dengan pihak pemerintah desa baralau kemudian tahap kedua dilalakukan pengumpulan data yang akan menjadi acuan dalam pembangunan website sistem informasi desa baralau dan tahap terakhir adalah melakukan perancangan dan pengembangan website. Dalam tahapan perancangan dan pengembangan website peneliti menggunakan metol waterfall. Hasil dari penelitian ini adalah pihak desa dapat memantau status pengajuan surat secara real-time, memberikan pemberitahuan kepada masyarakat tentang status pengajuan, dan meningkatkan transparansi proses administratif.